The Migration Crisis in the Local News: Evidence from the French-Italian Border - Silvia Peracchi (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the impact of local exposure to the migrant crisis on the local news market. Exploiting a narrow geographical setting, it explores a policy dating from June 2015, whereby French authorities introduced militarized controls at the Italian frontier. With the border controls in place, groups of migrants and asylum seekers who had planned to cross the border irregularly were pushed back to the Italian lands. With rejected migrants clustering at the border, natives residing along the Italian region were unevenly exposed to their settlement. Taking advantage of this unequal treatment as a natural experiment, this study uses novel data collected on the text and on the number of local news items for the border areas of Liguria, Italy, between 2011 and 2019. It documents that the backlog of migrants in the Italian border area was substantially mediatized: coverage of migration rose most in the most exposed municipalities. Conversely, anti-immigrant discourse in the news grew more in areas least directly in contact with the border. Exploring further this framing dimension, the bias effect turns out to be shaped by readers' demand and to be closely associated with local news penetration. Finally, this study documents that anti-immigrant slant and voting preferences share a similar broad direction, while a related broad pattern also appears in hate-crime records.
Keywords: F22; L82; F50; 330; media slant; EU borders; immigration; diff-in-diff